Application of Electron Beam Melting to the Removal of Phosphorus from Silicon: Toward Production of Solar-Grade Silicon by Metallurgical Processes - Hideaki Sasaki; Yoshifumi Kobashi; Takashi Nagai; Masafumi Maeda (Advances in Materials Science and Engineering)
Removal methods of impurity from metallurgical-grade silicon (Si) are intensively studied to produce solar-grade silicon (SoG-Si) with a smaller economical load and lower cost. Removal of phosphorus (P) has been an important issue because of difficulties in application of conventional metallurgical methods such as solidification refining. Because P evaporates preferentially from molten Si due to its high vapor pressure, electron beam (EB) melting has been applied to the purification of Si. The evaporation of impurity P from Si is considered based on previous thermodynamic investigations here, and several research reports on EB melting of Si are reviewed.